Isolation and definition of bacteria from fresh common carp Cyprinus carpio L. in Shatt al-Arab River: Isolasi dan definisi bakteri dari ikan mas segar (Cyprinus carpio L.) di Sungai Shatt al-Arab - Al- Shammari, Nadia A.H. (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Fish, particularly Cyprinus carpio, are vital to global food security and aquaculture economies due to their high protein content and widespread availability. Specific Background: However, these fish can harbor a range of bacterial pathogens, especially in environments like the Shatt al-Arab River, where pollution and aquaculture stressors may exacerbate microbial contamination. Knowledge Gap: There is limited localized data on the bacterial flora present in healthy common carp from this river system, particularly regarding potential human pathogens. Aims: This study aimed to isolate and identify bacterial species present in the skin, liver, and intestines of apparently healthy C. carpio from the Shatt al-Arab River. Results: A total of 122 bacterial isolates were identified using phenotypic methods and Vitek II, with Aeromonas hydrophila (13.93%), Vibrio spp. (12.29%), Staphylococcus aureus (12.29%), and Escherichia coli (11.47%) among the most prevalent. Novelty: The detection of high bacterial incidence in healthy fish, particularly fecal indicators, suggests significant environmental contamination and unrecognized risks to consumers. Implications: These findings underscore the need for improved water quality monitoring and hygienic handling practices in fisheries to prevent potential zoonotic infections and ensure public health safety.Highlight : The study identifies a high prevalence (85%) of bacteria in healthy Cyprinus carpio, highlighting public health risks from contaminated fish. Dominant bacteria included Aeromonas spp., Vibrio spp., E. coli, and Staphylococcus aureus, indicating possible fecal contamination. The intestine was the most bacteria-rich organ, suggesting it as a critical site for monitoring bacterial colonization in aquatic species. Keywords : Common carp, Aeromonas Species, Shatt al-Arab River, Gram-Negative Bacterial